Collective scattering of massive stars in higher order gravity - Hadjimichef, D. [UNESP]; Kokubun, F. [UNESP] (American Physical Society (APS), 1997)
In the weak field approximation of higher order gravity theory a gravitational potential is described by a Newtonian plus a Yukawa-like term. This new term is used to explain some aspects of galactic dynamics, without considering dark matter. Its presence modifies the scattering probability of a massive intruder star and relaxation time of the stellar system.